2011
DOI: 10.1016/j.apenergy.2011.06.054
|View full text |Cite
|
Sign up to set email alerts
|

A model predictive control strategy for load shifting in a water pumping scheme with maximum demand charges

Abstract: SUMMARYThe aim of this research is to affirm the application of closed-loop optimal control for load shifting in plants with electricity tariffs that include time-of-use (TOU) and maximum demand (MD) charges. The water pumping scheme of the Rietvlei water purification plant in the Tshwane municipality (South Africa) is selected for the case study. The objective is to define and simulate a closed-loop load shifting (scheduling) strategy for the Rietvlei plant that yields the maximum potential cost saving under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…They highlighted several DSM tools used to enhance system efficiency, such as: 1) information feedback and 2) dynamic pricing with or without direct load control (for example, time-of-use pricing, critical-peak pricing, peak-time rebate, real-time pricing and inclining block rate) [4]. Other studies emphasized load scheduling from on peak to off peak times as an effective tool for consumption reduction with the additional economic and environmental gains [5,6] or to achieve financial savings for the customers [7,8]. Panapakidis et al indicates that the wider deployment of smart meters is an important tool that can enhance DSM implementation and reduce household consumption [9].…”
Section: Introductionmentioning
confidence: 98%
“…They highlighted several DSM tools used to enhance system efficiency, such as: 1) information feedback and 2) dynamic pricing with or without direct load control (for example, time-of-use pricing, critical-peak pricing, peak-time rebate, real-time pricing and inclining block rate) [4]. Other studies emphasized load scheduling from on peak to off peak times as an effective tool for consumption reduction with the additional economic and environmental gains [5,6] or to achieve financial savings for the customers [7,8]. Panapakidis et al indicates that the wider deployment of smart meters is an important tool that can enhance DSM implementation and reduce household consumption [9].…”
Section: Introductionmentioning
confidence: 98%
“…Some applications consider load shifting by finding the optimal switching times of equipment or processes according to the TOU tariff, e.g., controlling conveyor belts [6,7], pumps [8,9], geysers [10] and equipment that form part of a batch process [11]. These examples show significant cost saving compared to the baseline case, but actual energy saving is very little because the objective is focused on load shifting from peak periods.…”
Section: Introductionmentioning
confidence: 99%
“…Although it does not guarantee global optimality of operations, it has yielded good control strategies in practice (Nikolaou 2001), acting against uncertainties in demand at each schedule update. It has also been applied as a control technique to mitigate maximum demand charges when operating a WDS (van Staden et al 2011). Other iterative methods, decompose the scheduling problem into sub-problems that can be solved by a range of mathematical optimisation methods.…”
Section: Review Of Mathematical Optimisation Approachesmentioning
confidence: 99%
“…Pump scheduling for fixed energy tariffs has been studied extensively, detailed reviews can be found in D' Ambrosio et al (2015) and Singh (2014). However, as energy grids are changing with the introduction of renewables, different operating strategies may be favourable compared to optimising for a fixed energy tariff.…”
Section: Introductionmentioning
confidence: 99%